High quality metal-quantum dot-metal structure fabricated with a highly compatible self-aligned process - 付英春 王晓峰 马刘红 周亚玲 杨香 王晓东 杨富华 (Journal of semiconductors, 2015)
A self-aligned process to fabricate a ＂metal-quantum dot-metal＂ structure is presented, based on an ＂electron beam lithography, thin film deposition and dry etching process＂. The sacrificial layers used can improve the lift-off process, and novel lithography layouts design can improve the mechanical strength of the fabricated nanostructures. The superiority of the self-aligned process includes low request for overlay accuracy, high compatibility with a variety of materials, and applicable to similar structure devices fabrication. Finally, a phase change memory with fully confined phase-change material node, with the length × width × height of 255 × 45 × 30 nm^3 was demonstrated.